The application of biochemical responses to assess environmental quality of tropical estuaries: field surveys - Alves Maranho, Luciane; Seabra Pereira, Camilo Dias; Choueri, Rodrigo Brasil; Cesar, Augusto; Gusso-Choueri, Paloma Kachel [UNESP]; Torres, Ronaldo Jose; de Souza Abessa, Denis Moledo [UNESP]; Morais, Rodofley Davino; Mozeto, Antonio Aparecido; Angel DelValls, Tomas; Laura Martin-Diaz, Maria (Royal Soc Chemistry, 2012)
A battery of biomarkers of exposure (EROD, DBF, GST and GPx) and effect (lipid peroxidation and DNA damage - strand breaks) were analyzed in gill tissues from caged and native oysters Crassostrea rhizophorae exposed to two tropical estuarine systems in SW Brazil: Santos (S1, S2, S3, S4) and Paranagua (P1 - control, P2, P3, P4). The exposure lasted 28 days. Native oysters were sampled in the same areas where caged systems were exposed. Significant induction of biomarkers of exposure to organic compounds and oxidative stress (p < 0.05) were observed in all transplanted individuals from Santos resulting in DNA damage and lipid peroxidation. Biological adverse effects were more evident in oysters transplanted in the Santos Estuarine System, a recognized contaminated area, than in the Paranagua Estuarine System, surrounded by urban areas and Environmental Protected Areas. Native specimens from both estuaries showed adaption to the impacts of several contamination sources affecting the ecosystem. The use of transplanted C. rhizophorae proved to be a suitable tool for assessing and monitoring the environmental quality in mangrove ecosystems. This integrated approach employing multi-biomarker responses under field conditions could be incorporated as a descriptor of health status in tropical estuarine systems.